Higher Photochemical Quenching and Better Maintenance of Carbon Dioxide Fixation Are Key Traits for Phosphorus Use Efficiency in the Wheat Breeding Line, RAC875 - Nguyen, Van Lam; Palmer, Lachlan; Stangoulis, James (Frontiers in Plant Science, 2022)
Maintaining carbohydrate biosynthesis and C assimilation is critical under phosphorus (P) deficiency as iorganic P (Pi) is essential for ATP synthesis. Low available P in agricultural soils occurs worldwide and fertilizer P sources are being depleted. Thus, identifying biosynthetic traits that are favourable for P use efficiency (PUE) in crops is crucial. This study characterised agronomic traits, gas exchange and chlorophyll traits of two wheat genotypes that differ in PUE. RAC875 was a P efficient genotype and Wyalkatchem was a P inefficient genotype. The plants were grown in pots under growth room conditions at two P levels; 10 mg P kg-1 soil (low P) and 30 mg P kg-1 soil (adequate P) and gas exchange and chlorophyll fluorescence were measured at the vegetative and booting stages using a portable photosynthesis system (LI-6800, Licor, USA). Results showed significant differences in some agronomic traits between the two wheat genotypes, i.e., greater leaf size and area, and a higher ratio of productive tillers to total tillers in RC875 when compared to Wyalkatchem. The CO2 response curve showed Wyalkatchem was more severely affected by low P than RAC875 at the booting stage. The relative ratio of the photosynthetic rate at low P to adequate P was also higher in RAC875 at the booting stage. Photochemical quenching (qP) in RAC875 was significantly higher when compared to Wyalkatchem at the booting stage. Maintaining CO2 fixation capacity under low P and higher qP would be associated with P efficiency in RAC875 and measuring qP could be a potential method to screen for P efficient wheat.